История и миф в романах О. Ипатовой - Cенькевич, Татьяна; Cenkevych, Tatiana (Волинський національний університет імені Лесі Українки, 2008)
Исследуется взаимодействие исторической и мифопоэтической моделей мира в структуре романов современной писательницы О. Ипатовой. Аргументируется мысль о расширении пространственно-временного континуума романов посредством актуализации образов, тем и мотивов первичной мифологии. The article investigates the interaction of the historical and mystical-poetical world’s models in the structure of the novels of the modern authoress O. Ipatova. Is argued the thought about widening spatial-temporal continuum of the novels by means of actualizing the images, themes and motives of primary mythology.
History and Myth in the Novels of Olga Ipatova
Keywords: первичная мифология; primary mythology; исторический роман; historical novel; гармонизация мира; world’s harmonization; синтез; synthesis